Review: The Potential for Development of Red Palm Oil Industry in East Kalimantan - Hamka Hamka; Bernatal Saragih; Deny Sumarna; Krishna P. Candra; Sukmiyati Agustin; Marwati Marwati (Riviera Publishing, 2024)
Food security is a critical aspect of development, especially in regions like East Kalimantan, Indonesia, where per capita food availability has declined since 2016. The oil palm industry, particularly Crude Palm Oil (CPO), plays a significant role in addressing food security issues by providing a major agricultural commodity that can be processed into various products including red palm oil, which is rich in nutrients like carotenoids, vitamin E, and essential fatty acids. This study aims to explore and analyze the potential development of the red palm oil industry in East Kalimantan. The research utilizes a literature review method, involving the analysis and synthesis of various sources such as scientific journals, reports, and statistical data to assess the potential and opportunities for developing the red palm oil industry in East Kalimantan. The findings indicate that red palm oil, with its high concentrations of beta-carotene and tocopherol, presents a significant opportunity for development in East Kalimantan. Red palm oil can serve as a nutritious alternative to traditional cooking oils and margarine. Despite its potential, the utilization of red palm oil in Indonesia remains limited, mainly restricted to cooking oil production. The study suggests that the development of the red palm oil industry could enhance food security and nutritional intake in East Kalimantan. By promoting red palm oil as a functional food and a nutraceutical product, it could offer a viable solution to improve the health and well-being of the community while also supporting sustainable agricultural practices.